Optical resonance of nanoantennas consisting of single nanoparticle and couple nanoparticle pair - Wu, Yu-Ming (2013)
Based on the finite integration technique, the optical resonant properties of single and couple nanoparticles of many shapes have been comprehensively investigated. Characterized by the surface plasmon resonance, these structures are proven to be nanoantennas operating in the optical range. Their optical properties are found to be dependent on various effects like the geometrical parameters of the nanoparticles and the excitation orientation. By developing the broadband calculation especially covering the visible and infrared range of the optical spectrum, we conducted sufficient comparable studies to demonstrate the adjustable nanoantenna performances. This study has potential applications in the microscopy, spectroscopy, and optoelectronic devices.